Atrial Fibrillation Detected After Acute Ischemic Stroke - Vita Kusuma Rahmawati; Mauliya Sri Sukmawati Wahyudi; Dwi Ayu Novinda Sari (Faculty of Medicine, University of Jember, 2022)
Atrial fibrillation (AF) increases 4-5 times incidence of cardiac embolic stroke. In contrast, as many as 70% of AF cases can be detected in stroke within three days of onset, and this can affect the patient's prognosis. This case report describes the causal pathophysiology of AF and acute stroke and identifies the associated risk factors. Case 1 is a 44-year-old woman, acute stroke with acute decrease level of consciousness. The patient came with status epilepticus and a hypertensive emergency. Obtained a history of stroke, uncontrolled hypertension, and myocardial infarction. Initial Score National Institutes of Health Stroke Scale (NIHSS) was 33 and CHA2DS2-VASc was 5. Investigation non-contrast head Computed Tomography (CT) scan showed no bleeding and echocardiography (ECG) showed AF with rapid ventricular response. The patient died after 3 days of treatment. Case 2 is an 83-year-old woman, acute stroke with acute decrease level of consciousness and right motor lateralization. There was a history of hypertension and stroke with left hemiparesis. The initial NIHSS was 28 and CHA2DS2-VASc was 6. Investigations non-contrast head CT scan showed no bleeding and ECG showed AF with normal ventricular response. The patient was discharged from the hospital after being treated for 22 days with NIHSS of 20. Several risk factors for post-stroke AF are elderly, hypertension, subtype of ischemic stroke, prior stroke, and comorbidities such as DM and hypertension. Post-stroke AF can occur because of changes in heart rhythm through autonomic disorders, increased plasma catecholamine levels, and inflammatory reactions. Early Recognition of risk factors, focusing on patients at higher risk of AF detected after stroke becomes important for comprehensive management of stroke with AF. Keywords: acute ischemic stroke, atrial fibrillation, CHA2DS2-VASc score, risk factors.